Spectrophotometric Determination of Vanadium(V) after Separation by Adsorption of its N-p-Bromophenylthiobenzohydroxamic Acid Complex on Microcrystalline Naphthalene - Kalwania, G.S.; Mathur, Rajiv; Shyam, Radhey; Mathur, Priya (Asian Journal of Chemistry, 2011)
The method of adsorption of N-p-bromophenylthiobenzohydroxamic acid vanadium(V) complex on microcrystalline naphthalene followed by a solid-liquid separation is described for the trace analysis of vanadium. This complex is stable in naphthalene dimethyl formamide solution. The absorbance has showed a linear relationship to the concentration of vanadium in the range 7-150 μg per 10 mL of dimethyl formamide. The molar absorptivity and sensitivity have been found to be 2.6 × 104 L mol-1 cm-1 and 0.01346 μg cm-2, respectively for the absorbance of 0.001 with a standard deviation of 0.17 %.